Dai Salons alle Esposizioni, alle aste di New York nel XIX secolo. Il caso di Ignacio León y Escosura - Marinella Pigozzi (Boletín del Museo del Prado)
The role played by salons, exhibitions, art dealers and critics in the dissemination of a nostalgic taste has recently begun to be examined. Paris, London and Rome were cities where every year operators of all kinds imported, restored, produced, sold or exported thousands of works, ancient, modern and contemporary, to Europe and the dynamic cities of the United States, including fake masterpieces meant for the most important collectors. In this article, we focus on the activity of the painter from Oviedo Ignacio León y Escosura, his connections with art dealers and his role as a disseminator of Spanish art. Furthermore, it corrects some errors related to his work and to the forge of fake artworks due to his connection with the Marcy family.